PENANAMAN NILAI-NILAI AKHLAK DALAM MATERI PENDIDIKAN AGAMA ISLAM DI KELAS VIII SEKOLAH MENENGAH PERTAMA NEGERI 26 SAROLANGUN - Sodri, Ahmad; Neni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is based on the importance of character formation in students amidst the increasingly complex development of the times, thus requiring the active role of teachers in instilling moral values through the learning process. This study aims to describe the installation of moral values in Islamic Religious Education material for eighth-grade students at SMP Negeri 26 Sarolangun. This research uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. The subjects of the research include Islamic Religious Education teachers and eighth-grade students. The research results show that the installation of moral values in Islamic Religious Education material is carried out through several strategies, namely PAI learning, advice, question and answer, assignment giving, reinforcement and reprimand, and exemplary stories. The moral values instilled include honesty, discipline, responsibility, politeness, and mutual respect. Supporting factors in instilling moral values include; a curriculum that incorporates character education, cooperation between teachers and the school, the use of engaging teaching methods, and school programs based on religious principles. Meanwhile, the inhibiting factors are the lack of awareness among some students and the influence of the external environment. In conclusion, the instillation of moral values in the Islamic Religious Education curriculum for the eighth grade at SMP Negeri 26 Sarolangun has been carried out quite well through various teaching strategies, although there are still some obstacles that need to be addressed.